PEMBELAJARAN KONTEKSTUAL BAHASA INGGRIS DALAM MENULIS IKLAN DENGAN APLIKASI CANVA - pujiasih, erna (Jurnal Riset Daerah, 2022)
Best practices in contextual learning by writing advertisementwith the Canva app aim to apply students' ability to write advertisement text with the Canva application. The method is qualitative descriptive. The data based on observation, implementation of learning, and questioner. The subjects of this study were students of class X SMA Negeri 1 Bantul. Based on the best practices in the learning, the teaching and learning process are explaining the advertising material, group activities in analyzing advertisements, writing advertisements individually with the Canva application, and presenting the results of their creativity. Based on the results of the questionnaire and the practice of writing advertisements with Canva, students are able to understand